Characterisation of environmental pollution by GC-MS analysis of polycyclic aromatic compounds in water and soil - Rohwer, Egmont Richard (University of Pretoria, 2013)
Thesis (PhD (Applied Science: Chemistry))--University of Pretoria, 2007.